Cross-cultural differences in academic self-efficacy and its sources across socialization contexts - Gebauer, Miriam Marleen; McElvany, Nele; Köller, Olaf; Schöber, Christian (Technische Universität Dortmund, 2021)
This study investigated how as reported by Bandura (Self-efficacy: The exercise of control Freeman, 1997) sources of self-efficacy differ across socialization contexts for German students with diverse immigrant backgrounds. We measured all four sources of academic self-efficacy in three socialization contexts for students of former Soviet Union and Turkish descent as well as without an immigrant background, assuming that we would find differences between these groups. Participants were 1217 seventh-grade students in Germany. Multigroup structural equation analyses with latent variables revealed the differential importance of socialization contexts for the relation between academic self-efficacy and its sources across groups. For students of former Soviet Union and Turkish descent, verbal or social persuasion is the strongest contributing factor for academic self-efficacy, whereas for students without an immigrant background, it is mastery experience. In the school context, significant relationships between sources of self-efficacy and academic self-efficacy could only be observed for students without an immigrant background. The results both support and refine Bandura’s social cognitive theory by showing that self-related constructs function differently in students with culturally diverse immigrant backgrounds.
Social psychology of education,;Band 24. 2021, Heft 6, Seiten 1407-1432
Keywords: Immigrant backgrounds; Socialization contexts; Sources of self-efficacy; Student academic self-efficacy; Social cognitive theory; 370; Migrationshintergrund; Selbstwirksamkeit |; Sozialisation |; Sozial-kognitive Lerntheorie |